Strategi Pengembangan Sumber Daya Manusia untuk Mengatasi Keterbatasan Tenaga Kerja di Risse Convection Sungai Pua Kabupaten Agam - Nadiatul Khaira; Era Sonita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research is motivated by the limited workforce at Risse Convection, where this convection has not been able to increase income significantly due to limited production capacity caused by a lack of qualified workforce. The aim of this research is to provide concrete recommendations for Risse Convection in developing an effective human resource development strategy to deal with workforce limitations and meet demand for sharia clothing products. The following is the essence of the research based on the problem formulation for copra entrepreneurs in Nagari Lansek Kadok: the majority of copra entrepreneurs in Nagari Lansek Kadok, South Rao District, Pasaman Regency, prioritize excellent service to customers and analyze the growth of their business to increase people's income. Because most of the residents of Nagari Lansek Kadok have lower middle class incomes, the community still views the purchase price given by the seller (copra entrepreneur) as reasonable. The business strategies of Nagari Lansek Kadok copra entrepreneurs, the factors that hinder these entrepreneurs, and the development strategies carried out by traders in this area are things that need to be improved if the residents of Nagari Lansek Kadok, South Rao District, Pasaman Regency can make improvements. to see an increase in their income. The reason behind this is that they continuously incorporate new ideas into the development of their company. Based on the research results, it can be concluded that the human resource development strategy to overcome the limited workforce in Risse Convection Sungai Pua, Agam Regency is: 1. Lack of workforce at Risse Konveksi resulted in reduced production of sharia clothing on the market, workforce competency occurred due to the lack of special training for employees, resulting in the work being completed more slowly or not on time. To overcome this problem, Risse Convection implements an annual reward system, and employee training is carried out personally. For new employees, Risse Convection uses its convection advantages in innovative sharia clothing designs to be able to recruit employees from the surrounding area or outside the village/nagari as well as the use of social media to promote new design innovations to reach a wider audience and increase brand visibility. 2. By using the SO (Strength-Opportunity) strategy method, namely optimizing existing strengths by taking advantage of existing opportunities. The SO (Strength-Opportunity) strategy that can be applied in increasing employment at Risse Convection is: utilizing excellence in innovative sharia clothing design to recruit employees from the surrounding area or outside the village/nagari and maintaining an annual reward system for employees who work hard to improve motivation and productivity.